2022
DOI: 10.3390/ma16010109
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of As-Aged Mg-Zn-Sn-Mn-Al Alloys

Abstract: The microstructure and mechanical properties of as-aged Mg-6Zn-4Sn-1Mn-xAl (ZTM641-xAl, x = 0, 0.2, 0.5, 1, 2, 3 and 4 wt.%) alloys are studied in this paper. In terms of microstructure, the results reveal that the addition of Al mainly leads to the formation of the Al8Mn5, Al11Mn4, Al2Mg5Zn2 and Mg32(Al,Zn)49 phases. With increases in the addition of Al, the average grain size first decreases and then increases, while the undissolved phases increase. The average grain size of the ZTM641-0.5Al alloy is the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…The results show that the grain sizes decrease and then increase with the increase in Al element content, and the addition of Al elements can promote the formation of second phases such as Al 8 Mn 5 , Al 11 Mn 4 , Mg 32 (Al,Zn) 49 , Al 2 Mg 5 Zn 2 , and MgZn. However, in this study, the Al-Mn phases possess an Al 3 Mn 2 structure, which is not consistent with that reported in the literature [46][47][48][49]. And the combination of Mn and Zn would be changed for the Al addition.…”
Section: Introductioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The results show that the grain sizes decrease and then increase with the increase in Al element content, and the addition of Al elements can promote the formation of second phases such as Al 8 Mn 5 , Al 11 Mn 4 , Mg 32 (Al,Zn) 49 , Al 2 Mg 5 Zn 2 , and MgZn. However, in this study, the Al-Mn phases possess an Al 3 Mn 2 structure, which is not consistent with that reported in the literature [46][47][48][49]. And the combination of Mn and Zn would be changed for the Al addition.…”
Section: Introductioncontrasting
confidence: 95%
“…Secondly, it can be found that the α-Mn dispersoids disappear and are replaced by Al 3 Mn 2 particles. Ye, Hou, and Deng reported the Al 8 Mn 5 and Al 11 Mn 4 in the Mg-6Zn-4Sn-1Mn-xAl alloys [46][47][48][49]. However, no studies have been reported on the formation of the Al 3 Mn 2 phase in Mg-Zn-Sn-Mn-Al alloy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure (a), we can see that the one-stage aged ZTM641-0.2Ca alloy has the highest strength, with the UTS and YS being 392 MPa and 365 MPa, respectively. According to our previous research [ 21 ], the UTS and YS of the one-stage aged ZTM641-0.2Al alloy are 382 MPa and 352 MPa, and the UTS and YS of one-stage aged ZTM641-0.5Al alloy are 350 MPa and 299 MPa. When 0.5% Al is added to the alloy, the strength and plasticity show a decreasing trend, while the UTS and YS are 365 MPa and 325 MPa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…When the alloy is deformed, the coordinating deformation ability of the alloy is poor, resulting in a decrease in the strength of the alloy. [21], the UTS and YS of the onestage aged ZTM641-0.2Al alloy are 382 MPa and 352 MPa, and the UTS and YS of one-stage aged ZTM641-0.5Al alloy are 350 MPa and 299 MPa. When 0.5% Al is added to the alloy, the strength and plasticity show a decreasing trend, while the UTS and YS are 365 MPa and 325 MPa, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 94%